Light-Induced Actuation of Poly(dimethylsiloxane) Filled with Graphene Oxide Grafted with Poly(2-(trimethylsilyloxy)ethyl Methacrylate) - Osicka, Josef; Mrlik, Miroslav; Ilčíková, Markéta; Munster, Lukas; Bazant, Pavel; Špitalský, Zdenko; Mosnáček, Jaroslav (Polymers, 2018)
This study serves to combine two approaches into one single step, to achieve a significant improvement of the light-induced actuation capabilities. Graphene oxide (GO) is an inert material, from the electrical and thermal conductivity point of view, and is incompatible with the usually-used poly(dimethylsiloxane) (PDMS) matrix. During surface-modification by surface-initiated atom transfer radical polymerization, the GO was transformed into a conducting and compatible material with the PDMS showing enormous light-induced actuation capability. The GO surface-modification with poly(2-(trimethylsilyloxy)ethyl methacrylate) (PHEMATMS) chains was confirmed by transmission electron microscopy and thermogravimetric analysis, with an on-line monitoring of gasses using FTIR. The improved compatibility was elucidated using contact angle and dielectric properties measurements. The PHEMATMS shell was investigated using gel permeation chromatography and nuclear magnetic resonance. The improved electric conductivity was measured using the four-point probe method and by Raman spectroscopy. The very important mechanical properties were elucidated using dynamic mechanical analysis, and with the help of thermo-mechanic analysis for the light-induced actuation. The excellent actuation capabilities observed, with changes in the length of around 0.8% at 10% pre-strain, are very promising from the point of view of applications.
Keywords: dielectrics; reduction; dynamic mechanical analysis; graphene oxide; SI-ATRP; light-induced actuation